Cognitive alterations associated with hormone therapy in patients with breast cancer: A systematic review - Denisa Toader, Irina; Antonio Cruzado, Juan (Psicooncología, 2024)
Objective: to determine the cognitive alterations associated with hormone therapy in breast cancer patients. Methods: the present work consists of a systematic review of international experimental studies on the effects of hormone therapy on cognitive functions in women with breast cancer, following the PRISMA statement. Strict methodological criteria were followed for its selection, including only longitudinal studies with baseline and/or control group evaluations. Results: despite the discrepancies described, the results show significant impairment in verbal memory, executive functions, verbal learning, and processing speed. Conclusions: for future research it is recommended to use stricter methodological criteria and to carry out long-term follow-ups, considering that the average time of administration of these treatments’ ranges between 5 and 10 years.
Keywords: Breast cancer; hormone therapy; cognitive functions; cognitive impairment; aromatase inhibitors; SERMS